Effect of preoperative chemotherapy on the outcome of women with operable breast cancer. Issue 10 (1st April 2023) - Fisher, B; Bryant, J; Wolmark, N; Mamounas, E; Brown, A; Fisher, E R; Wickerham, D L; Begovic, M; DeCillis, A; Robidoux, A; Margolese, R G; Cruz, A B; et al.
Abstract : PURPOSE: To determine, in women with primary operable breast cancer, if preoperative doxorubicin (Adriamycin) and cyclophosphamide (Cytoxan; AC) therapy yields a better outcome than postoperative AC therapy, if a relationship exists between outcome and tumor response to preoperative chemotherapy, and if such therapy results in the performance of more lumpectomies. PATIENTS AND METHODS: Women (1, 523) enrolled onto National Surgical Adjuvant Breast and Bowel Project (NSABP) B-18 were randomly assigned to preoperative or postoperative AC therapy. Clinical tumor response to preoperative therapy was graded as complete (cCR), partial (cPR), or no response (cNR). Tumors with a cCR were further categorized as either pathologic complete response (pCR) or invasive cells (pINV). Disease-free survival (DFS), distant disease-free survival (DDFS), and survival were estimated through 5 years and compared between treatment groups. In the preoperative arm, proportional-hazards models were used to investigate the relationship between outcome and tumor response. RESULTS: There was no significant difference in DFS, DDFS, or survival (P = .99, .70, and .83, respectively) among patients in either group. More patients treated preoperatively than postoperatively underwent lumpectomy and radiation therapy (67.8% v 59.8%, respectively). Rates of ipsilateral breast tumor recurrence (IBTR) after lumpectomy were similar in both groups (7.9% and 5.8%, respectively; P = .23). Outcome was better in women whose tumors showed a pCR than in those with a pINV, cPR, or cNR (relapse-free survival [RFS] rates, 85.7%, 76.9%, 68.1%, and 63.9%, respectively; P < .0001), even when baseline prognostic variables were controlled. When prognostic models were compared for each treatment group, the preoperative model, which included breast tumor response as a variable, discriminated outcome among patients to about the same degree as the postoperative model. CONCLUSION: Preoperative chemotherapy is as effective as postoperative chemotherapy, permits more lumpectomies, is appropriate for the treatment of certain patients with stages I and II disease, and can be used to study breast cancer biology. Tumor response to preoperative chemotherapy correlates with outcome and could be a surrogate for evaluating the effect of chemotherapy on micrometastases; however, knowledge of such a response provided little prognostic information beyond that which resulted from postoperative therapy.